Subcranial and orthognathic surgery for obstructive sleep apnea in achondroplasia. Issue 12 (December 2017) - Susarla, Srinivas M.; Mundinger, Gerhard S.; Kapadia, Hitesh; Fisher, Mark; Smartt, James; Derderian, Christopher; Dorafshar, Amir; Hopper, Richard A.
Abstract: Purpose: Obstructive sleep apnea (OSA) is a common problem in patients with achondroplasia. The purpose of this study was to assess changes in airway volumes following various degrees of facial skeletal advancement. Methods: This was a retrospective evaluation of patients with achondroplasia who underwent facial skeletal advancement for obstructive sleep apnea. Patients were treated with either an isolated Le Fort III distraction (LF3) or Le Fort II distraction with or without subsequent Le Fort I and bilateral sagittal split osteotomies (LF2 ± LF1/BSSO). Demographic, cephalometric, volumetric, and polysomnographic variables were recorded pre- and postoperatively. Results: Six patients with achondroplasia underwent midface advancement for treatment of OSA (2 LF2 + LF1/BSSO, 2 LF2, 2 LF3). Patients undergoing LF2 + LF1/BSSO had consistent volumetric improvements at the nasopharyngeal and oropharyngeal levels (Δ ≥ +347% and ≥+253%, respectively). Patients undergoing LF2 alone had consistent improvement in the nasopharyngeal airway alone (Δ ≥ +214%). Patients undergoing LF3 alone had consistent, but less dramatic, changes in nasopharyngeal volume (Δ ≥ +97.1%). All patients undergoing LF2 distraction (with or without LF1/BSSO) had a ≥50% reduction in the apnea–hypopnea index (AHI) postoperatively; there was no improvement in AHI with LF3 alone. Conclusion: In patients with achondroplasia-associated OSA there are variable improvements in airway volume. This preliminary report suggests that LF2 distraction, with or without subsequent LF1/BSSO, may provide consistent reductions in AHI relative to LF3 distraction.